MANAJEMEN KEUANGAN PUBLIK PADA DANA DESA DALAM MEWUJUDKAN KETAHANAN PANGAN DI DESA CIBIRU WETAN KABUPATEN BANDUNG TAHUN 2024 - Berlian Anggreini; Dede Sri Kartini; Iyep Saefulrahman (Journal Publicuho, 2025)
This study aims to determine the activities of the Cibiru Wetan Village Government in its success in managing public finances for village funds in realising food security, as evidenced by the award for anti-corruption model villages and villages with good food security status. The approach used is descriptive qualitative with Indra Bastian's public financial management model, which includes fund acquisition activities, fund utilisation activities, and asset management activities. The results show that in fund acquisition activities, the Cibiru Wetan Village Government obtained village funds from the central government (external) amounting to 20% of the 2024 fiscal year village fund ceiling for food security. Funds were used by providing village funds to beneficiary groups, namely the Women Farmers Group, egg-laying chicken farmers, sheep farmers, cattle farmers, and the purchase of curly chili seeds. In asset management, there were three parties that benefited: the Cibiru Wetan Village Government with an increase in village revenue (PADes), beneficiary groups with increased group income, and the general public with easier access to food.